Theory of Risk- and Double-Risk- Society and its Application to the Diagnosis of the Development of Lithuanian Society - Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2002)
This paper aims at diagnosing the current state and change of Lithuanian society from the perspective of a theory of risk-society (Beck, 1992) and reflexive modernization (Beck, Giddens, Lash, 1994). Paper illuminates a ‘double-risk’ character of Lithuanian society arguing that contemporary transitional and developing societies, e.g. Lithuanian, are turning into ‘risk-societies’ not after the urgent issues of social distribution of ‘goods’ are resolved, as the risk-society theory would suggest in the case of Western affluent societies. By contrast, a ‘double-risk’ society is characterised by mutual acuteness and inter-twined importance of both kinds of societal issues: creation and distribution of social welfare (‘goods’) as well as reduction and social distribution of risks (‘bads’). A double-risk society, similarly as a risk society is characterized by decreasing unquestionable faith in the modern institutions of science and technology, whereas a double risk-society is characterized by the painful and complex processes of transition from state-socialism that leads to disillusionment in other institutional pillars of modern society, namely the market economy and democratic governance. At the same time, a double-risk society encompasses and reflects most of the features pertaining to the risk-society – depleting social and geographical ‘boundaries vis-a-vis societal exposure to the variety of risks (environmental, nuclear); increasing importance of sub-politics with its characteristic aspects-vested interests and manipulative capacity of certain professions to shape social perceptions of risk; and decreased societal faith in the capacity of modern institutions of science and technology to cope with the globalizing risks.